1995
DOI: 10.1007/bf00932419
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopy studies onOnchocerca jakutensis andO. flexuosa of red deer show different host-parasite interactions

Abstract: Adult filariae of two intranodular Onchocerca species of red deer (Cervus elaphus) were examined at the ultrastructural level. In all, 90 nodules of O. flexuosa and 20 nodules of O. jakutensis were studied by histology. O. jakutensis caused cystic and pus-filled nodules in which the female and male worms were motile. Female worms possessed a thick cuticle and a well-developed somatic musculature. The basal lamina of the muscular syncytia was connected with the transhypodermal fibers through long protrusions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…In view of TEM evidence of Wolbachia presence in M. ozzardi (Kozek and Raccurt 1983), this finding questions whether Wolbachia is uniformly present in all filarial species of a genus. In favour of the species-specific occurrence of endosymbionts is the lack of evidence of intracellular bacteria in Onchocerca flexuosa (Plenge-Bo¨nig et al 1995;Henkle-Du¨hrsen et al 1998), whereas they have been found in at least nine other species of this genus (Taylor and Ho¨rauf 1999).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In view of TEM evidence of Wolbachia presence in M. ozzardi (Kozek and Raccurt 1983), this finding questions whether Wolbachia is uniformly present in all filarial species of a genus. In favour of the species-specific occurrence of endosymbionts is the lack of evidence of intracellular bacteria in Onchocerca flexuosa (Plenge-Bo¨nig et al 1995;Henkle-Du¨hrsen et al 1998), whereas they have been found in at least nine other species of this genus (Taylor and Ho¨rauf 1999).…”
Section: Discussionmentioning
confidence: 94%
“…However, whereas it has been found in most of the major pathogenic filariae in humans, namely Onchocerca volvulus, Wuchereria bancrofti, and Brugia malayi, it has been shown by means of PCR that two filarial species non-pathogenic to humans, namely the rodent filaria Acanthocheilonema viteae and the deer filaria Onchocerca flexuosa appear to be free of these symbionts (McLaren et al 1975;Plenge-Bo¨nig et al 1995;Bandi et al 1998;Henkle-Du¨hrsen et al 1998). So far, it remains unclear, whether Loa loa and Mansonella perstans, both to a certain extent pathogenic to humans Mommers et al 1994,;Churchill et al 1996) also harbour Wolbachia, thus potentially opening new insights into the pathogenicity of these diseases and offering a novel drug target.…”
Section: Introductionmentioning
confidence: 94%
“…These considerations lead us to conclude that the mutualistic phenotype in filariae arose as a result of Wolbachia colonizing the somatic hypodermal cords. The most probable fitness benefit was an increase in the reproductive lifespan of the worms, since females of O. volvulus (and almost certainly O. ochengi) remain fecund for >10 yr, whereas O. flexuosa is thought to only live for ;1 yr (Plenge-Bönig et al 1995). As reactive oxygen species are one of the principal drivers of aging (Buttemer et al 2010), we propose that the ability of Wolbachia to perform aerobic respiration and to metabolize iron while maintaining an elevated oxidative stress response are key mechanisms that promote infection of somatic tissues in filariae.…”
Section: Discussionmentioning
confidence: 99%
“…If the absence of W. pipientis in L. yutajensis will be confirmed, this nematode will represent a new case of a species which does not harbor W. pipientis while being closely related with species which do. Indeed, there is already such an example in filarial nematodes: O. flexuosa does not harbor W. pipientis, while other species in the genus Onchocerca do (Plenge-Bönig et al, 1995 andHenkle-Dührsen et al, 1998). L. yutajensis could become an interesting model in the study of the relationship between W. pipientis and its nematode hosts, as well as in investigations on the immuno-pathological role of this bacterium in the course of filariasis.…”
Section: Discussionmentioning
confidence: 99%
“…Kozek, 1977 andHenkle-Dührsen et al, 1998). These two approaches have not revealed the presence of W. pipientis in Onchocerca flexuosa, but representatives of this species have not yet been examined by PCR (Plenge-Bönig et al, 1995 andHenkleDührsen et al, 1998). Assuming the monophyly of the Onchocerca group, the absence of W. pipientis in O. flexuosa could be interpreted as a secondary loss of bacteria in the phylogenetic lineage leading to this species.…”
Section: Introductionmentioning
confidence: 99%